2017
DOI: 10.1038/s41598-017-03355-y
|View full text |Cite
|
Sign up to set email alerts
|

Yolk removal generates hatching asynchrony in snake eggs

Abstract: Hatching synchrony is wide-spread amongst egg-laying species and is thought to enhance offspring survival, notably by diluting predation risks. Turtle and snake eggs were shown to achieve synchronous hatching by altering development rates (where less advanced eggs may accelerate development) or by hatching prematurely (where underdeveloped embryos hatch concurrently with full-term embryos). In Natricine snakes, smaller eggs tend to slow down metabolism throughout incubation in order to hatch synchronously with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…While further investigations are needed to address this question, there is evidence that incubation times (at 28 °C) are heavily constrained in the viperine snake (i.e. always remain within a 24 h boundary, irrespective of experimental treatments; Aubret et al . 2016a,b, 2017) and early hatching may entail deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While further investigations are needed to address this question, there is evidence that incubation times (at 28 °C) are heavily constrained in the viperine snake (i.e. always remain within a 24 h boundary, irrespective of experimental treatments; Aubret et al . 2016a,b, 2017) and early hatching may entail deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…LE and EHE treatment half clutches were placed in a plastic container (20 cm × 15 cm × 5 cm) on a 2 cm layer of wet vermiculite (1:5 water to vermiculite by volume) and incubated in two identical incubation chambers (ExoTerra Model PT‐2445, Rolf C. Hagen Inc., USA) set at a constant 28 °C, a temperature successfully used for artificially incubating eggs of the viperine snake (Aubret 2013; Aubret et al . 2016a, 2017). Water bowls placed within each incubator ensured ambient humidity remained at 100% throughout incubation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yolk serves as a nutritional resource used by embryos and recently hatched young for structural growth and maintenance of tissues. The amount of yolk that gets allocated toward these separate functions may vary systematically, such as by environmental temperature (Storm & Angilletta, ), and could influence hatchling size and metabolism (Aubret et al, ; Storm & Angilletta, ). For example, embryonic growth rate in Magdalena river turtles ( Podocnemis lewyana ) positively correlates with yolk lipids (Páez et al, ), while female painted turtles ( Chrysemys picta ) allocate more protein and lipid to the yolks of their early season clutch than to their late season clutch (Harms et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the influence of diet composition on neurotransmission may impact the development of individual behavior (Wauben & Wainwright, ), and a higher state of nutrition may correlate with more active behavioral types (Han & Dingemanse, ). A recent study in a Natricine snake model ( Natrix maura ), showed a direct relationship between available yolk mass and hatchling metabolism, and demonstrated that the availability of yolk reserves can affect how those resources are utilized by the embryo and subsequent hatchling (Aubret et al, ). Although growth rate, metabolism, and other phenotypic attributes can be influenced by properties of the yolk (e.g., mass, lipid levels), how nutritional reserves and behavior are linked is less clear, and warrants exploration.…”
Section: Introductionmentioning
confidence: 99%